Positron emission tomography-computed tomography versus positron emission tomography-magnetic resonance imaging for diagnosis of oral squamous cell carcinoma: A pilot study - Schlittenbauer, Tilo; Zeilinger, Martin; Nkenke, Emeka; Kreißel, Sebastian; Wurm, Matthias; Lell, Michael; Kuwert, Torsten; Beck, Michael (Journal of Cranio-Maxillofacial Surgery, 2015)
Diagnostic imaging of head and neck cancer has made enormous progress during recent years. Next to morphological imaging modalities (computed tomography [CT] and magnetic resonance imaging [MRI]), there are also hybrid imaging systems that combine functional and morphological information (positron emission tomography [PET]/CT and PET/MRI). The aim of this study was to compare the diagnostic accuracy of PET/MRI in the diagnosis of head and neck cancer with other imaging modalities (MRI, CT, PET/CT). Ten patients (nine male and one female) with histologically proven oral squamous cell carcinoma participated in an 18 F-FDG-PET/CT scan and an additional 18 F-FDG PET/MRI scan prior to surgery. The morphological and functional results were compared with the histological results. Inclusion criteria were histologically proven oral squamous cell carcinoma and no prior surgical intervention, medical therapy, or local external radiation. There was no significant correlation between tumor differentiation and maximum standard uptake values. Functional imaging showed a slightly better correlation with the measurement of the maximal tumor diameter, whereas pure morphological imaging showed a better correlation with the measurement of infiltration depth. Only with PET/MRI could correct lymph node staging be reached; the other imaging tools showed false-negative or false-positive results. In conclusion, we showed in our limited patient cohort that PET/MRI is superior to the morphological imaging modalities, especially for lymph node staging.
EVALuna2:13832